Incidence of gestational diabetes mellitus in the United Arab Emirates; comparison of six diagnostic criteria: The Mutaba’ah Study - Bashir, Maryam M.; Ahmed, Luai A.; Elbarazi, Iffat; Loney, Tom; Al-Rifai, Rami H.; Alkaabi, Juma M.; Al-Maskari, Fatma (Frontiers in Endocrinology, 2022)
Background: For more than half a century, there has been much research and controversies on how to accurately screen for and diagnose gestational diabetes mellitus (GDM). There is a paucity of such updated research among the Emirati population in the United Arab Emirates (UAE). Lack of uniform GDM diagnostic criteria results in the inability to accurately combine or compare the disease burden worldwide and locally. This study aimed to compare the incidence of GDM in the Emirati population using six diagnostic criteria for GDM. Methods: The Mutaba’ah study is the largest multi-center mother and child cohort study in the UAE with an 18-year follow-up. We included singleton pregnancies from the Mutaba’ah cohort screened with the OGTT at 24-32weeks from May 2017 to March 2021. We excluded known and newly diagnosed diabetics. GDM cumulative incidence was determined using the six specified criteria. GDM risk factors were compared using chi-square and t tests. Agreements among the six criteria were assessed using kappa statistics. Results: 2,546 women were included with a mean(±SD) age of 30.5±6.0 years. Mean(±SD) gravidity was 3.5±2.1, and mean(±SD) BMI at booking was 27.7±5.6 kg/m2. GDM incidence ranged from 8.4% according to EASD 1996 criteria to 21.5% according to NICE 2015 criteria. The two most inclusive criteria were the NICE 2015 and the IADPSG criteria with GDM incidences of 21.5% (95% CI 19.9, 23.1) and 21.3% (95% CI 19.8, 23.0), respectively. Agreement between the two criteria was moderate (k = 0.66; p<0.001). The least inclusive was the EASD 1996 criteria [8.4% (95% CI 7.3, 9.6)]. The locally recommended IADPSG/WHO 2013 criteria had weak to moderate agreement with the other criteria, with Cohen's kappa coefficient ranging from (k = 0.51; p<0.001) to (k = 0.71; p<0.001). Most of the GDM risk factors assessed were significantly higher among those with GDM (p<0.005) identified by all criteria. Conclusions: The findings indicate discrepancies among the diagnostic criteria in identifying GDM cases. This emphasizes the need to unify GDM diagnostic criteria in this population to provide accurate and reliable incidence estimates for healthcare planning, especially since the agreement with the recommended criteria was not optimal.